Pulmonary embolism four days after interruption of therapy with rivaroxaban - Göndör, Gabor; Stöllberger, Claudia (Phlebologie, 2018)
Thrombosis after cessation of anticoagulation, also named rebound thrombosis, is a matter of concern and controversy. There are only few published data about occurrence of rebound thrombosis associated with non-vitamin K-antagonist oral anticoagulant drugs (NOACs). We report on a 58-year-old male with paroxysmal atrial fibrillation (AF) with a CHA2DS2VASC score of 4 who developed central pulmonary embolism four days after interruption of rivaroxaban because of parotid surgery. He had received 40 mg enoxaparin/d. The parotid gland was partially resected within 6 hours without blood loss. Pulmonary embolism and AF occurred on the first postoperative day. He recovered with low-molecular-weight heparin in therapeutic dosages and amiodarone and was discharged with phenprocoumon.The relevance of a rivaroxaban rebound phenomenon, manifesting as arterial embolism, stroke or venous thromboembolism should be clarified. It should be assessed if rebound-phenomena also exist for the NOACs dabigatran, apixaban and edoxaban. Thus, the randomized trials and registries investigating patients with AF or venous thromboembolism should be re-analysed and, based on these data, recommendations should be developed for situations in which NOAC-therapy has to be interrupted or ceased.
Keywords: Non-vitamin K-antagonist; oral anticoagulants; rivaroxaban rebound phenomenon; atrial fibrillation; pulmonary embolism